Brain drain or brain gain? Micro evidence from an African success story - Cátia Batista; Aitor Lacuesta; Pedro C. Vicente (Institute for the Study of Labor (IZA), 2007)
Does emigration really drain human capital accumulation in origin countries? This paper explores a unique household survey purposely designed and conducted to answer this specific question for the case of Cape Verde - the African country with the largest fraction of tertiary educated population living abroad, despite also having a fast-growing stock of human capital. Unlike previous literature, our tailored survey allows us to adjust existing inflated brain drain numbers for educational upgrading of emigrants after migration. We do so by combining our survey data on current, return and non-migrants with information from censuses of the destination countries. Our micro data also enables us to propose a novel, explicit test of brain gain arguments according to which the possibility of own future emigration positively impacts educational attainment in the origin country. Crucially, the innovative empirical strategy we propose hinges on the ideal characteristics of our survey, namely on full histories of migrants and on a new set of exclusion restrictions to control for unobserved heterogeneity of emigrants. Our results point to a very substantial impact of the brain gain channel on the educational attainment of those left behind. Alternative channels (namely remittances, family disruption, and general equilibrium effects at the local level) are also considered, but these do not seem to play an important role. Overall, we find that there may be substantial human capital gains from allowing free migration and encouraging return migration.
Keywords: 330; Brain drain; brain gain; brain circulation; international migration; human capital; effects of emigration in origin countries; household survey; Cape Verde; sub-Saharan Africa; Brain Drain; Humankapital; Makroökonomischer Einfluss; Afrika südlich der Sahara